Youtube as a Learning Media Islamic Education - Zartiyana, Nurfitri; Agustina, Maya; Hasan, Khairuddin (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
This study aims to determine the usefulness and management of YouTube which is used as a learning medium for Islamic Religious Education, as well as the audience's response to YouTube accounts that discuss PAI material. The method in this study uses a qualitative approach with a descriptive method. Data collection is carried out through literature study techniques, observation, and documentation on YouTube channels that discuss PAI material. This study analyzed six YouTube Channels related to Islamic Religious Education learning content. The results showed that the use of YouTube as a tool for teachers in explaining PAI material can make it easier for teachers to find teaching materials that are in accordance with the demands of the times. The management of interesting PAI learning media on YouTube is managed by uploading videos and designing content as interesting as possible so that it can be enjoyed by users who use YouTube for their learning needs. Then the response to using YouTube in PAI learning was very liked with positive comments from the Channel. So that YouTube is used as a search medium for PAI material, as an additional medium in finding information related to the material you want to learn, as well as to increase student motivation in learning.